Evidence-based clinical practice in nursing and health care : assimilating research, experience and expertise - Pearson, Alan, 1948-; Field, John, RPN.; Jordan, Zoe.; Wiley InterScience (Online service) (Oxford ; Malden, MA : Blackwell Pub., 2007)
'Evidence-Based Clinical Practice in Nursing and Health Care examines the Joanna Briggs Institute model of evidence-based health care which recognises research, theory and practice as sources of evidence, and takes a practical approach to developing, implementing and evaluating practice, based on'evidence' in its broadest sense.''Evidence-Based Clinical Practice in Nursing and Health Care addresses the generation and synthesis of evidence, and the transferral and utilisation of evidence in clinical practice. It describes the development of practice information sheets and clinical guidelines and provides practical guidance on the implementation of evidence-based practice and its evaluation using clinical audit.'--Jacket.
The evolution of evidence-based practice -- A comprehensive approach to evidence-based health care : the JBI model -- What is evidence for practice? -- Health care evidence generation -- Evidence synthesis : the systematic review -- Evidence synthesis : critical appraisal, data extraction and the synthesis of findings -- Evidence transfer : writing up a systematic review report and developing clinical guidelines -- Evidence utilisation : implementing evidence-based guidelines -- Evidence utilisation : clinical audit -- Evidence-based practice : issues and challenges.
Includes bibliographical references (pages 167-172) and index.
Print version record.
Keywords: Joanna Briggs Institute for Evidence Based Nursing and Midwifery; Evidence-Based Nursing; Evidence-Based Medicine; Nursing Care -- methods; Evidence-Based Medicine -- methods; Models, Nursing; Nursing; Soins infirmiers factuels; Médecine factuelle; Electronic books